Upper limit of normal serum alanine aminotransferase levels in Japanese subjects. Issue 12 (17th February 2014) - Tanaka, Kenichi; Hyogo, Hideyuki; Ono, Masafumi; Takahashi, Hirokazu; Kitajima, Yoichiro; Ono, Naofumi; Eguchi, Takahisa; Fujimoto, Kazuma; Chayama, Kazuaki; Saibara, Toshiji; Anzai, Keizo; Eguchi, Yuichiro; et al.
Abstract : Aim: Serum alanine aminotransferase (ALT) is important for screening, diagnosis and management of chronic liver diseases. The incidence of non‐alcoholic fatty liver disease (NAFLD)/non‐alcoholic steatohepatitis (NASH), which is considered a hepatic manifestation of lifestyle‐related diseases, is increasing worldwide. However, the upper limit of the normal ALT level has not yet been established because of not excluding many lifestyle‐related diseases. The aim of this study was to evaluate the upper limit of normal serum ALT levels in Japanese subjects. Methods: We analyzed the serum ALT levels of 11 404 Japanese subjects negative for hepatitis B surface antigen and hepatitis C virus antibody, and who received health check‐ups. Lifestyle factors related to ALT levels were determined by multivariate analysis. Subjects with all factors identified by multivariate analysis within the normal range were defined as "healthy" subjects. The 90th percentile of ALT levels in healthy subjects was defined as the upper limit of normal ALT. Results: Whereas alcohol intake was not a significant factor, the following were independently associated with ALT concentration by multivariate analysis: sex; age; body mass index; waist circumference; concentrations of total cholesterol, high‐density lipoprotein cholesterol, triglycerides and fasting blood glucose; and fatty liver on ultrasonography. Healthy subjects consisted of 1462 (21.2%) men and 2046 (45.4%) women, and the 90th percentiles of the ALT levels in the two groups were 29 and 23 IU/L, respectively. Conclusion: The upper limits of normal ALT when considering lifestyle factors in Japanese subjects were 29 IU/L in men and 23 IU/L in women.